Physicochemical characterization of water-soluble polysaccharide of Pachyrhizus erosus L. with fermentation assisted extraction method. (May 2019) - Rusmarilin, H; Hilman, A
Abstract: Water-soluble polysaccharide (WSP) is one of a complex chemical content contained in Pachyrhizus erosus L. (PeL). A recent study was examined the effect of FAEM with aqueous and Saccharomyces sp. In this study used a completely randomized design with two factors i.e. water extraction with extracting water addition on the amount of starch used (1:0.5; 1:1; 1:1.5; 1:2) and FAEM with distilled water, Saccharomyces sp and Rhizopus sp . Interestingly, dextrose equivalent of WSP-PeL (DE = 4) showed increased significant effect of FAEM with Rhizopus sp than both distilled water and Saccharomyces sp. Although degree of polymerization and total sugar just showed significant effect, WSP-PeL (DPav = 24) has a good solubility (SO = 83%) and viscosity (µ = 0.973 cP). These findings suggest that due to the viscous properties of WSP-PeL can inhibits the absorption of excessive macronutrient and decrease blood sugar levels, derived from fermentation WSP-PeL in the colon to produce Saturated-Chain Fatty Acid (SCFA).